Oil Retention in Shales: A Review of the Mechanism, Controls and Assessment - Feng, Yue; Xiao, Xianming; Wang, Enze; Sun, Jian; Gao, Ping (Frontiers in Earth Science, 2021)
Shale oil is a vital alternative energy source for oil and gas and has recently received an extensive attention. Characterization of the shale oil content provides an important guiding significance for resource potential evaluation, sweet spot prediction, and development of shale oil. In this paper, the mechanism, evaluation and influencing factors of oil retention in shales are reviewed. Oil is retained in shales through adsorption and swelling of kerogen, adsorption onto minerals and storage in shale pores. Quite a few methods are developed for oil content evaluation, such as three-dimensional fluorescence quantitation, two-dimensional nuclear magnetic resonance (2D NMR), solvent extraction, pyrolysis, multiple extraction-multiple pyrolysis-multiple chromatography, logging calculation, statistical regression, pyrolysis simulation experiment, and mass balance calculation. However, the limitations of these methods represent a challenge in practical applications. On this basis, the influencing factors of the oil retention are summarized from the microscale to the macroscale. The oil retention capacity is comprehensively controlled by organic matter abundance, type and maturity, mineral composition and diagenesis, oil storage space, shale thickness, and preservation conditions. Finally, oil mobility evaluation methods are introduced, mainly including the multitemperature pyrolysis, 2D NMR, and adsorption-swelling experiment, and the influencing factors of movable shale oil are briefly discussed. The aim of this paper is to deepen the understanding of shale oil evaluation and provide a basis for further research.